Unveiling the impacts of geopolitical risk on the transition to the decentralized financial landscape - Nikos K. Kyriazēs; Emmanouil Marios L. Economou (Peace Economics, Peace Science and Public Policy (PEPS), 2025)
This paper examines the dynamic interplay between the global geopolitical risk and eleven decentralized finance (DeFi) digital currencies during the inflationary burden caused by the Russia-Ukraine war episodes. Daily data spanning from 13 October 2021 to 29 October 2024 and the innovative Quantile-Vector Autoregressive (Q-VAR) methodology are employed for estimating the pairwise, joint and network linkages at the lower, middle and upper quantiles. High levels of geopolitical risk are more connected with bull markets of the DeFi assets and new war episodes strengthen this relation. Geopolitical tensions combined with high inflation lead to the GPR becoming major determinant of DeFi markets so contributing to the transition to the digital decentralized cashless financial system. Maker is the leading DeFi asset in this transition and constitutes a promising successor of fiat currencies that suffer from devaluation generated by conflicts.
Keywords: E44; E52; F30; G15; H56; 320; cashless economy; decentralized finance; dynamic connectedness; geopolitical risk; inflation; Russia-Ukraine war